Outdoor Learning in Elementary Schools: Utilizing the Surrounding Environment to Increase Student Learning Engagement - Bagus Cahyanto; Qita Riambada Tsurayya Dewi; Oktaviani, Ella; Titis Angga Rini; Nindya Nurdianasari; Saleh, Hairus (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
This research aimed to reveal various reasons that encourage teachers to use outdoor learning, the implementation of outdoor learning in schools, obstacles, and the positive impact of implementing outdoor learning at SDN 2 Tajinan. Researchers employed a descriptive qualitative approach, where data collection was carried out through interviews, observation, and documentation. The research results showed that the reasons teachers use outdoor learning include increasing learning engagement, providing authentic learning experiences, honing skills, and introducing students to the environment. Apart from that, outdoor learning is carried out to connect theory and practice in everyday life, create contextual learning, and develop social skills, problem-solving, and students' curiosity. Outdoor learning is carried out by inviting students to plant plants in the school environment, visiting the Arhanud Education Center in Batu City, and inviting students to get to know the environment around the school. The obstacles faced by teachers are difficulties in conditioning students due to the large number of students and the weather and natural conditions. Apart from that, implementing outdoor learning requires more thorough preparation and tends to take longer than conventional learning. The positive impacts that arise include being able to increase student enthusiasm and involvement in learning, making learning more lively, and increasing students' social-emotional aspects, responsibility, and concern for the environment.